(untitled) (Studia theodisca, 2013)
This essay investigates the poetic strategies that Nelly Sachs introduces into her lyrical drama Eli in order to solve the problem of the ethical limitations of Holocaust literary representation in the post-Auschwitz world. Sachs rejects Adorno’s famous dictum and voices the “unspeakable” and the “unthinkable” through Romantic themes and the Jewish tradition. The shift from “visible” to “invisible” allows her to elaborate the Holocaust, to preserve collective memory, to confirm the destiny of the Jewish people, and to legitimate the role of literature after Auschwitz as a fusion of word and myth, functional to analyzing reality on a critical level.